2‐arachidonoylglycerol levels are increased in leukocytospermia and correlate with seminal macrophages. (11th November 2016) - Barbonetti, A.; Bisogno, T.; Battista, N.; Piscitelli, F.; Micillo, A.; Francavilla, S.; Maccarrone, M.; Francavilla, F.
Summary: Evidence has been produced that macrophages can actively generate endocannabinoids (eCBs) in response to inflammatory stimuli. As eCBs are involved in the control of several physiological processes, including reproduction, here, we explored whether seminal levels of the eCBs, N ‐arachidonoylethanolamine (AEA), and 2‐arachidonoylglycerol (2‐AG), were higher in the presence of leukocytospermia, and were correlated with semen concentration of macrophages. The content of AEA and 2‐AG was measured by high‐performance liquid chromatography/mass spectrometry in seminal plasma of ejaculates from 18 leukocytospermic patients (>1 × 10 6 leukocytes/mL) and 21 normozoospermic controls. In the same ejaculates, round cells were phenotyped by flow‐cytometry as leukocytes (CD45+), macrophages (CD14+), and activated macrophages (CD14+, HLA‐DR+). The levels of 2‐AG, but not of AEA, were significantly higher in ejaculates from leukocytospermic patients than in controls and exhibited a significant correlation with semen concentration of macrophages and activated macrophages. Significant associations of 2‐AG with macrophages and activated macrophages persisted after adjustment for semen volume and sperm concentration. In conclusion, here we provide evidence that seminal plasma levels of 2‐AG are higher in the presence of leukocytospermia, as a marker of macrophages activation. Further studies are warranted to elucidate possible clinical implications.